Assessment of Testing and Treatment of Asymptomatic Bacteriuria Initiated in the Emergency Department. (3rd November 2020) - Petty, Lindsay A; Vaughn, Valerie M; Flanders, Scott A; Patel, Twisha; Malani, Anurag N; Ratz, David; Kaye, Keith S; Pogue, Jason M; Dumkow, Lisa E; Thyagarajan, Rama; Hsaiky, Lama M; Osterholzer, Danielle; et al.
Abstract: Background: Reducing antibiotic use in patients with asymptomatic bacteriuria (ASB) has been inpatient focused. However, testing and treatment is often started in the emergency department (ED). Thus, for hospitalized patients with ASB, we sought to identify patterns of testing and treatment initiated by emergency medicine (EM) clinicians and the association of treatment with outcomes. Methods: We conducted a 43-hospital, cohort study of adults admitted through the ED with ASB (February 2018–February 2020). Using generalized estimating equation models, we assessed for (1) factors associated with antibiotic treatment by EM clinicians and, after inverse probability of treatment weighting, (2) the effect of treatment on outcomes. Results: Of 2461 patients with ASB, 74.4% (N = 1830) received antibiotics. The EM clinicians ordered urine cultures in 80.0% (N = 1970) of patients and initiated treatment in 68.5% (1253 of 1830). Predictors of EM clinician treatment of ASB versus no treatment included dementia, spinal cord injury, incontinence, urinary catheter, altered mental status, leukocytosis, and abnormal urinalysis. Once initiated by EM clinicians, 79% (993 of 1253) of patients remained on antibiotics for at least 3 days. Antibiotic treatment was associated with a longer length of hospitalization (mean 5.1 vs 4.2 days; relative risk = 1.16; 95% confidence interval, 1.08–1.23) and Clostridioides difficile infection (CDI) (0.9% [N = 11] vs 0% [N = 0]; P = .02). Conclusions: Among hospitalized patients ultimately diagnosed with ASB, EM clinicians commonly initiated testing and treatment; most antibiotics were continued by inpatient clinicians. Antibiotic treatment was not associated with improved outcomes, whereas it was associated with prolonged hospitalization and CDI. For best impact, stewardship interventions must expand to the ED. Abstract : Among hospitalized patients with ASB, the majority of urine testing and treatment was initiated by emergency medicine clinicians and often continued by inpatient clinicians. Antibiotic treatment was associated with Clostridioides difficile infection and longer duration of hospitalization.